Effects of endogenous abscisic acid on fruit growth and ripening of coloured capsicum (Capsicum annuum) - Prajapati, Uma; Asrey, Ram; Sharma, R R (The Indian Journal of Agricultural Sciences, 2019)
The present study was conducted at ICAR-IARI, New Delhi in the year 2016–17 to ascertain the role of abscisic acid (ABA) on fruit growth and ripening in capsicum. ABA was estimated at five fruit developmental stages of yellow and red coloured varieties. Irrespective of varieties higher level of ABA was recorded at 1st stage which later on showed slight reduction at 2nd and 3rd stages and thereafter, registered further sharp rise at 4th stage. Respiration rate was higher in earlier stages and later it decreased up to two fold in fifth stage. Total chlorophyll was reduced in successive developmental stages while carotenoid increased. Total carotenoid content was found to be ABA dependent and it increased with elevation in fruit's ABA content. The results indicated that ABA plays a vital role not only in fruit ripening but in early fruit growth of capsicum too.